Robust gate assignment to minimise aircraft conflicts. Issue 1 (31st December 2023) - Du, Wenbo; Zhu, Shaochuan; Tong, Lu (Carol); Cai, Kaiquan; Liang, Zhe
Abstract : Robust gate assignment problem (RGAP) aims to generate a reliable schedule that reduces the occurrence of potential gate conflicts under stochastic flight delays. Although allocating buffer time in the gate schedules is widely adopted to absorb the delay disturbances, the relation between the schedule robustness and the aircraft delay heterogeneity has not yet been well explored. To allocate the buffer optimally, we analyse the heterogeneity of gate conflict and propose two new robustness measurements to quantify the number of potential conflicts from the expectation perspective. Then the RGAP is modelled as a set-covering problem to simultaneously optimise the expected conflict cost and basic operating cost. To solve the model efficiently, we develop a column generation-based heuristic (CDBH) to find high-quality solutions. Computational studies based on Shenzhen Baoan International Airport reveal that the proposed measurements considering the delay heterogeneity can significantly improve the robustness of gate schedules.